An experimental model of open tibial fracture in the New Zealand white rabbit: surgical technique - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Ibrahim, Mohd Zulfadzli; Che Seman, Che Nor Zarida; Zainal Abdullah, Muhamad Ezham (Tissue Engineering and Regenerative Medicine Society of Malaysia (TESMA), 2017)
The objective of this study was to induce open tibial fracture in New Zealand White Rabbit model via exposing the fracture site for six hours. Our hypothesis was that infection would be induced when the underlying bone is exposing for six hours. In this research, we performed open tibial fracture via anterolateral approach by exposing the underlying tibial bone for six hours to induced open fracture related with infection. The microbial assessments were performed for infection evaluation. After 24 hours of incubation, colonies were noted. The bacteriology consists of assessment using gram stain, coagulase and catalase tests to confirm the staphylococcus aureus. No death due to surgical complication was noted. The outcome of this study revealed infection can occur at fracture site according to this approach. An easier and simple method of surgery to create open fracture exposed for six hours to create infection. This approach is recommended for future open tibial fracture related infection surgery in New Zealand White rabbits.